Yes, We Can! Women as the ICT Control Taker and User - Meike Lusye Karolus; Isyfi Afiani (Yayasan Jurnal Perempuan, 2016)
The segregation between men and women in technology as the impact of the assumption that technology is masculine leads to the paradigm that reveals the technology and its use as the man-thing. In this regard, the ICT (Information and Communication Technology) is most likely playing the same role toward the paradigm of man-thing. Consequently, many women experience the gender discrimination in the cyber space. We the women are getting less space in using and maximizing ICT. There are several efforts of women in order to take part in the ICT world. This research aims to narrate the women who have taken control and maximized the use of ICT as a tool and media to deliver the message as well as knowledge in order to encourage themselves and other women in the field where they are in. This research belongs to descriptive qualitative research by conducting the concept of cyber feminism as the scoping study deals with how the cyber space is used as the media to encourage women. In result, this research shows that the women are able to take control and maximize the use of ICT under the pressure of social and political construction tied in patriarchal morality in cyber space.